Ethnic Los Angeles - Bozorgmehr, Mehdi; Waldinger, Roger David (Book collections on Project MUSE., 1996)
Ethnic Los Angeles presents a multi-investigator study of Los Angeles's immigrant population. Using U.S. census data for the past three decades, essays on each of L.A.'s major ethnic groups tell us where these new Americans live and work, why they came to Los Angeles, and the nature of their families and social networks. The contributors also give a history of immigration policy and discuss the economic forces that have made the city a magnet for immigrants.